Zdrazhko A. Y. Еvaluation criteria of the translation of children’s literature - Zdrazhko A. Y. (Philological Treatises, 2020)
E. Chesterman’s system of translation evaluation is given in the article, an attempt to complement and widen the given system for evaluation and characterization of children’s literature translation is also performed.